Study of the Use of Gas Diffusion Anode with Various Cathodes (Cu-Ag, Ni-Co, and Cu-B Alloys) in a Microbial Fuel Cell - Paweł P. Włodarczyk; Barbara Włodarczyk (Energies, 2024)
Advancing microbial fuel cell (MFC) technologies appears to be a crucial direction in bolstering wastewater treatment efforts. It ensures both energy recovery (bioelectricity production) and wastewater pre-treatment. One of the problems in the widespread use of MFCs is the generation of a small amount of electricity. Hence, a pivotal concern revolves around enhancing the efficiency of this process. One avenue of investigation in this realm involves the selection of electrode materials. In this research, a carbon-based gas diffusion electrode (GDE) was used as the anode of MFC. Whereas for the cathode, a copper mesh with various catalysts (Cu-B, Ni-Co, and Cu-Ag) was used. This research was conducted in glass MFCs with the sintered glass acting as a chamber separator. This research was conducted for various electrode systems (GDE/Cu-Ag, GDE/Ni-Co, and GDE/Cu-B). This study analyzed both the electrical parameters and chemical oxygen demand (COD) reduction time. In each case (for each electrode system), bioelectricity production was achieved. This work shows that when GDE is used as the anode and Cu-B, Ni-Co and Cu-Ag alloys as the cathode, the most efficient system is the GDE/Cu-Ag system. It ensures the fastest start-up, the highest power density, and the shortest COD reduction time.